Seasonal Variability May Affect Microbial Decomposers and Leaf Decomposition More Than Warming in Streams - Duarte, Sofia (2016)
Ongoing climate change is expected to affect the diversity and activity of aquatic microbes, which play a key role in plant litter decomposition in forest streams. We used a before-after control-impact (BACI) design to study the effects of warming on a forest stream reach. The stream reach was divided by a longitudinal barrier, and during 1 year (ambient year) both stream halves were at ambient temperature, while in the second year (warmed year) the temperature in one stream half was increased by ca. 3 °C above ambient temperature (experimental half). Fine-mesh bags containing oak (Quercus robur L.) leaves were immersed in both stream halves for up to 60 days in spring and autumn of the ambient and warmed years. We assessed leaf-associated microbial diversity by denaturing gradient gel electrophoresis and identification of fungal conidial morphotypes and microbial activity by quantifying leaf mass loss and productivity of fungi and bacteria. In the ambient year, no differences were found in leaf ecomposition rates and microbial productivities either between seasons or stream halves. In the warmed year, phosphorus concentration in the stream water, leaf decomposition rates, and productivity of bacteria were higher in spring than in autumn. They did not differ between stream halves, except for leaf decomposition, which was higher in the experimental half in spring. Fungal and bacterial communities differed between seasons in both years. Seasonal changes in stream water variables had a greater impact on the activity and diversity of microbial decomposers than a warming regime simulating a predicted global warming scenario.